The principles & processes of interactive design - Steane, Jamie (Bloomsbury, 2014)
"The Principles and Processes of Interactive Design is for new designers from across the design and media disciplines who need to learn about the fundamental principles and processes behind designing for digital media. This book is intended as both a primer and companion guide, that covers the design essentials from a digital perspective: user-based design research and development, digital colour and image, typography and hypertextuality, working with digital formats, screen-based grids and layouts, and storyboards and system mapping, as well as offering general guidance on how to present your ideas. Featured contributors include: Moving brands;The Chase; Happy Cog; Red Bee; BBC iPlayer; Imaginary Forces; and Bibliotheque Design"-- Provided by publisher.